Existing and Evolving Bioethical Dilemmas, Challenges, and Controversies in Vascularized Composite Allotransplantation: An International Perspective From the Brocher Bioethics Working Group. Issue 9 (September 2019) - Magill, Gerard; Benedict, James; Plock, Jan A.; Krones, Tanja; Gorantla, Vijay S.
Abstract : Early results of hand and face transplants and other grafts such as those of uterus, penis, trachea, larynx, or abdominal wall have confirmed the potential for vascularized composite allotransplantation (VCA) to restore appearance, anatomy, function, independence, and social integration in patients suffering from devastating tissue deficits untreatable by conventional treatment options. Despite such promise, these novel and complex procedures face challenges and controversies that remain open to discussion and debate. Indeed, many barriers to clinical advancement and negative stakeholder perceptions still exist. The bioethical challenges surrounding VCA include but are not limited to justice and vulnerability of subjects, and their experiences with risks, benefits and outcomes, provider economy of fame, public awareness and attitudes toward transplantation, and policy and regulatory issues shaping progress of the field. The First International Workshop on Bioethical Challenges in Reconstructive Transplantation was organized by the Brocher Foundation in Hermance, Switzerland. VCA professionals representing teams from across the world examined bioethical issues in VCA related to standards for safety, efficacy, feasibility, privacy, confidentiality, and equitability. Key discussion topics from the workshop were included in a survey questionnaire implemented across VCA professionals attending the 13th Congress of International Society of VCA held in Salzburg, Austria. The insights from the Brocher workshop and International Society of VCA survey as presented here could help inform the future development of clinical practice and policy strategies in VCA to ensure value, accessibility, and acceptance of these procedures by potential donors, potential or actual recipients and their families, and providers and payers.